Advances in understanding imbibition characteristics of shale using an NMR technique: a comparative study of marine and continental shale. (25th April 2018) - Yang, Liu; Dou, Ninghui; Lu, Xiaobing; Zhang, Xuhui; Chen, Xu; Gao, Jian; Yang, Chengwei; Wang, Yang
Abstract: Studying the imbibition characteristics of shale contributes to understanding the low flowback efficiency (<20%) and its potential effects on gas production. Previous studies have mainly focused on imbibition characteristics of marine shale, but few investigations have been conducted on continental shale to explore the microscopic imbibition mechanism. This paper performs a series imbibition experiments on typical sandstone, marine, and continental shale samples. The water migration and distribution is monitored by the nuclear magnetic resonance technique. For the same type of shale (marine or continental shale), the imbibition rate has a positive relationship with the clay mineral content. But continental shale contains more clay minerals and has a larger imbibition rate than marine shale. The expansion of clay minerals may have different impacts on the pore structure of marine and continental shale as the T2 spectra present. In contrary to non-swelling sandstone with constant T2 values, the T2 values of marine and continental shale vary during water imbibition. The T2 values of marine shale increase gradually due to the extension of microfractures, which can enhance the water imbibition rate and gas flowing channels significantly. However, the T2 values of continental shale decrease gradually as a result of destruction of matrix pores, which can decrease the water imbibition rate and have negative effects on gas flow channels. Compared with continental shale, the low flowback efficiency induced by water imbibition may be more suitable for marine shale to get good shale gas production. These findings can help understand the special imbibition characteristics of marine and continental shale.